A Significant Improvement in the Mechanical Properties of AISI 304 Stainless Steel by a Combined RCSR and Annealing Process. Issue 3 (23rd December 2016) - Asghari‐Rad, Peyman; Nili‐Ahmadabadi, Mahmoud; Shirazi, Hassan; Hossein Nedjad, Syamak; Koldorf, Sebastian
Abstract : The effect of a new severe plastic deformation method, "repetitive corrugation and straightening by rolling (RCSR)" on AISI 304 stainless steel is investigated. A thermo‐mechanical treatment based on the reversion of α′‐martensite is applied to produce fine‐grained structure. Microstructural characterizations are conducted by X‐ray diffraction and electron backscattered diffraction. Mechanical properties are investigated by measuring uniaxial tensile properties. It was found that the amount of strain‐induced martensite increases monotonically with increasing of applied strain, yielding up to 90 vol% of martensite after 30 cycles of the RCSR process. By applying a subsequent annealing, austenite grain size is decreased considerably, which leads to substantial strengthening. Abstract : 304 stainless steel is subjected to a new severe plastic deformation method named as RCSR. Microstructural evolutions and mechanical properties are investigated during a thermo‐mechanical process. Results show that the amount of strain‐induced martensite is controlled by RCSR cycles and could be reached to 90 vol% after 30 cycles, which, significantly improves the mechanical properties.